CD16+моноциты в прогнозе ответа на интраназальную иммунотерапию у пациентов с цереброваскулярной патологией - Shevela, E. Ya.; Ostanin, A. A.; Tikhonova, M. A.; Davydova, M. N.; Meledina, I. V.; Chernykh, E. R. (Патогенез, 2022)
Тезисы конференции